Gardens of the Mughal Empire - Smithsonian Institution (2002)
[Dt.:] "Gardens of the Mughal Empire" ist eine interaktive Webseite über die Gärten der Mogule, eine islamische Dynastie, die zwischen 1526 und 1858 in Südasien herrschte. Die Webseite ist das Ergebnis eines mehrjährigen Projektes, das neue Dokumente und Informatioen über wichtige Gärten in und um Lahore erschlossen hat. Es stellt auch eine Bibliographie über das Thema und eine Chronologie über die historische Geographie der Stadt Lahore während der Mogulzeit zur Verfügung. Die Seite bietet auch Zugriff auf eine Einführung in die Musik der Mugalzeit (Dhrupad). - [Engl.:] 'Gardens of the Mughal Empire' is an interactive web site on the Gardens of the Mughals, an Islamic dynasty that ruled between 1526 and 1858 in territories now divided among Pakistan, Afghanistan, Kashmir, and northern India. The web site is one result of a multi-year project that has provided substantial new documentary information for important Mughal garden sites in and near Lahore, Pakistan. It also provides a bibliography on the subject and a chronology of the historical geography of Mughal Lahore. An introduction to the Music of the Mugal Empire is given and can be listend online.